Social polyandry among siamangs: the role of habitat quality. (November 2017) - Lappan, Susan; Andayani, Noviar; Kinnaird, Margaret F.; Morino, Luca; Nurcahyo, Anton; O'Brien, Timothy G.
Abstract : In species where females do not associate spatially with other females, males usually range over an area including the home ranges of multiple females or defend the home range of one female. Nevertheless, social polyandry (multimale–unifemale grouping) occurs in some species. We examine an ecological constraints model relating habitat quality to facultative social polyandry in siamangs, Symphalangus syndactylus, by testing predictions of two hypotheses: (H1) variation in the size and density of important food trees affects the size of siamang home ranges and areas of exclusive use; (H2) socially polyandrous groups benefit from cooperative defence of the home range and area of exclusive use. Crown volume/ha of freestanding or strangler figs ( Ficus ), the most important siamang food, was negatively related to the size of the home range but not to the size of the area of exclusive use. Density and crown volume/ha of the second-most important plant food, Dracontomelon dao, was not related to the size of the home range or to the size of the area of exclusive use. Multimale groups had larger home ranges and areas of exclusive use than unimale groups, and the home ranges and areas of exclusive use of multimale groups encompassed more freestanding or strangling figs than those of unimale groups. Models of home range size including fig abundance (density or crown volume/ha) and the number of males as predictor variables suggested that multimale groups have larger home ranges than predicted by the relationship between fig abundance and home range size alone. While some other facultatively polyandrous species have larger home ranges in areas of poorer habitat quality, our results suggest a more complex situation for siamangs at our study site. Specifically, the density of large figs may constrain siamang ranging patterns, but multimale groups live in home ranges with more figs than those of unimale groups. Our results suggest that multimale groups may defend higher-quality territories than unimale groups. Highlights: We examined relationships among ecological variables, ranging and number of males. Ficus crown volume/ha was negatively related to home range (HR) size. Two-male groups had larger HRs and areas of exclusive use (AEU) than one-male groups. HR and AEU of two-male groups contained more freestanding or strangling Ficus . Two-male groups were larger and had more immature individuals than one-male groups.